Cyclic Stretch Negatively Regulates IL-1β Secretion Through the Inhibition of NLRP3 Inflammasome Activation by Attenuating the AMP Kinase Pathway - Maruyama, Kentaro; Sakisaka, Yukihiko; Suto, Mizuki; Tada, Hiroyuki; Nakamura, Takashi; Yamada, Satoru; Nemoto, Eiji (Frontiers in Physiology, 2018)
Macrophages are immune cells of hematopoietic origin that play diverse roles in host defenses and tissue homeostasis. In mechanical microenvironments, macrophages receive mechanical signals that regulate various cellular functions. However, the mechanisms by which mechanical signals influence the phenotype and function of macrophages in the process of inflammation have not yet been elucidated in detail. We herein examined the effects of cyclic stretch on NLR family, pyrin domain-containing 3 (NLRP3) inflammasome activation in J774.1, a murine macrophage cell line, and mouse primary bone marrow-derived macrophages. We showed that cyclic stretch inhibited adenosine monophosphate (ATP)-stimulated interleukin (IL)-1β secretion in lipopolysaccharide (LPS)-primed macrophages using ELISA and Western blot analyses. Cyclic stretch did not affect the degradation of the Inhibitor of κB or the nuclear translocation/transcriptional activity of nuclear factor (NF)-κB, suggesting that cyclic stretch-mediated inhibition was independent of the NF-κB signaling pathway. Consistent with these results, cyclic stretch did not affect the LPS-induced expression of inflammasome components, such as pro-IL-1β and NLRP3, which is known to require the activation of NF-κB signaling. We showed that the cyclic stretch-mediated inhibition of IL-1β secretion was caused by the suppression of caspase-1 activity. The addition of compound C, a specific inhibitor of adenosine monophosphate-activated protein kinase (AMPK), to LPS-primed macrophages inhibited IL-1β secretion as well as caspase-1 activation, suggesting that AMPK signaling is involved in ATP-triggered IL-1β secretion. Furthermore, the phosphorylation of AMPK induced by ATP in LPS-primed macrophages was significantly suppressed by cyclic stretch, indicating that cyclic stretch negatively regulates IL-1β secretion through the inhibition of caspase-1 activity by attenuating the AMPK pathway. Our results suggest that mechanical stress functions to maintain homeostasis through the prevention of excessive inflammasome activation in macrophages in mechanical microenvironments.